The level of knowledge on dietary supplements among patients of pharmacies in the Greater Poland region - Przysławskki, Juliusz; Stępczak, Mateusz; Reszelska, Monika; Wichura-Demska, Agnieszka (Journal of Medical Science, 2016)
Introduction. An appropriately balanced and varied diet should cover the body’s demand for energy and all necessary nutrients. In case of health disorders caused by malnutrition, a change of eating patterns or introduction of temporary dietary supplements containing deficient nutrients should be considered. Aim. Assessment of the level of knowledge among patients of pharmacies in Poznań/Greater Poland on nutritional supplements and factors which influence or decide about their use in everyday life. Material and Methods. A study concerning the use of dietary supplements was conducted on the basis of an original survey in a group of 401 persons, both men and women. The survey consists of 17 single choice questions and one multiple choice question. In order to assess preferences within the scope of use of a chosen group of supplements, a five-grade hedonic scale was used. Results. The study showed that most patients considered their knowledge to be at least at a good level. Those results were not confirmed by an objective assessment of their knowledge. The most preferred supplements were products including Omega-3 and Omega-6 acids, vitamin D, probiotics and prebiotics, calcium and vitamin and mineral complexes. The preferences among women and men in relation to the choice of specific groups of dietary supplements were similar. Conclusion. The study showed a varied level of knowledge on dietary supplements – especially on the legal aspects of their introduction on the market. The general level of knowledge on supplements was higher in the group of women.